Consumption of Fruit Before Meals with Different Glycaemic Index to Lipid Profile and Blood Glucose Levels in Overweight Adults - Ningrum, Neldawati; Indarto, Dono; Suminah, - (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Overweight increase the risk of non-communicable diseases. Lack of vegetables and fruit intake, and high consumption of sweet, fatty, and fried foods can increase the risk of overweight. Fruit contains high fiber and active compounds useful for controlling lipid profiles and blood glucose control. Objective: To identify the effect of consuming fruit before meals with different glycaemic index (GI) on lipid profiles and fasting blood glucose (FBG) levels in overweight adults. Methods: This experimental research used a pre-post control group design. The participants in this study were 43 overweight adults who were divided into 4 groups, control group, high GI group, moderate GI group, and low GI group. Each treatment group was given fruit with a different GI for 21 days. Measurement of lipid profile and blood glucose was done 3 times on day-1, day-14, and day-21. Results: Consumption of fruit before eating with low GI for 21 days reduced 14.56 mg/dl cholesterol, 30.4 mg/dl triglycerides, 23.55 mg/dl LDL, and 22.33 ml/ dl FBG. The fruit intervention with low GI also increased 3.89 mg/dl HDL. Conclusion: Consumption of fruit with low GI before meals can help control lipid profile and FBG. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 320-327